Switchable dual-wavelength Q-switched fiber laser based on sputtered indium tin oxide as saturable absorber - Zalkepali, N.U.H.H.; Awang, N A; Latif, A.A.; Zakaria, Z.; Yuzaile, Y.R.; Mahmud, N.N.H.E.N. (Elsevier, 2020)
This paper demonstrate experimentally the generation of a stable switchable dual-wavelength Q-switched fiber laser. The pulsed fiber lasers is generated from deposited Indium Tin Oxide (ITO) saturable absorber (SA) on fiber ferrule, which is prepared by using DC Magnetron Sputtering. The deposited ITO SA is then being sandwiched in between the two fiber ferrules. A stable switchable dual-wavelength is generated by the aid of two cascaded fiber Bragg gratings (FBGs). To achieve a flexible switched in individual wavelength of 1532 or 1533 nm and simultaneously dual-wavelength fiber laser, the in line polarization controller is utilized to control the mode competition in the fiber laser cavity. The proposed fiber laser is capable of generating output at the pump power of 118.10 mW, centered at wavelength 1532 nm. The proposed design is having a repetition rate of 48.30 kHz and a pulse width of 5.22 μs. Similarly, at 1533 nm, it generates a repetition rate of 25.61 kHz and a pulse width of 7.72 μs. The output is also observed to remain unchanged over time, indicating high stability with the signal to noise ratio of 52.70 dB and 52.00 dB at wavelength 1532 nm and 1533 nm, respectively. The combination between ITO and cascaded FBG can offer a feasible and straightforward candidate for a multiwavelength fiber laser according to these results. Laser radar and terahertz generation may become a few of the potential fields that related to this work.